A Protocol for The Effective Utilization of Energy in Wireless Sensor Network - Anand, Santosh; RR, Akarsha (International Journal of Engineering and Technology, 2018)
Energy utilization is an important aspect in any Wireless Sensor Network .The data transmission from various components connected over real-time networks consumes more energy in Wireless Sensor Network. Mainly the task of any network engineer lies in performing an energy efficient, so to reserve the nonrenewable energy supply to sensor nodes. The research convey out effective utilization of energy in wireless sensor networks. It is important to comprise long-term and low-cost monitoring in different WSN application. The network algorithms separated mainly in two parts, first to generate multiple paths and second to switch paths from generated list of paths .Which is implemented as multi-hop-communication so that the battery life of the sensor node may live for long term and low cost of monitoring, which achieve the high lifetime of WSN.Â